Correlation of Winter Temperature at Tripoli City, Shahāt, Sebhā and Al-Kufra Sites (Libya) and Large Scale Tele-Connection Indices - Ali, Abdalla Abdulhafid M.; Meiloud, Haifa M. Ben (The Libyan Journal of Science, 2020)
The impact of two winter atmospheric large scale tele-connection indices; North Atlantic Oscillation (NAO) and Arctic Oscillation (AO), on winter temperature at four different locations in Libya is presented. Winter temperature data series for 31 years (1980-2010) were analyzed using two different correlation analysis techniques. One is parametric (Pearson Correlation method) and the other is non-parametric (Spearman Correlation method). A scatter plot display along with the magnitude comparison between Pearson’s and Spearman’scoefficients showed that the relationship is linear. Winter temperature at all sites is negatively correlated to both NAO and AO. It is evident that the calculated Pearson’s correlation coefficients is large and highly significant compared to Spearman’s coefficients which are less in magnitude and low in significance, particularly for the correlation with AO. The results indicate that the inverse relationship of NAO and AO with the winter temperatures is stronger in the southern than in the northern regions. Mediterranean seawater could have played an important role in the modulation of coastal regions’ winter temperatures. According to the obtained results, NAO and AO should certainly be considered as important factors in determining winter temperature variability in Libya although other factors (beyond the scope of this study) might have some role.